Entrusting Children to Grandmothers: Exploring Care Dynamics through Multiple Roles of Women in Eastern Indonesia - Ekawati, Lenny Lia; Wijaya, I Nyoman Indra Kresna; Delpada, Benidiktus (Humaniora, 2024)
This paper investigates the practice of entrusting children to relatives in Alor Tengah Utara, Alor Regency. It highlights the socio-economic factors compelling parents to work away from home. Often, this leads to parents leaving their children in the care of their grandparents. Despite the stagnant economic growth in Alor regency, many young individuals migrate in search of better opportunities, creating a dynamic where women, particularly grandmothers, become “double mothers” by caring for both their own and entrusted children. Conducted from June 2021 to July 2022, this ethnographic study reveals the challenges and economic vulnerabilities these households face, exacerbated by the inadequate intergenerational care provided by ageing grandmothers or inexperienced young female relatives. The findings highlight the need for more equitable caregiving arrangements and support for these families, shedding light on a practice deeply rooted in being a cultural responsibility yet fraught with economic and emotional complexities.